Răspuns :
26. b + c = 7
2a + ab + ac = 63
2a + a (b+c) = 63
2a + 7a = 63
9a = 63
a = 7
27. a = 2
3b + 3c + ab + ac = 30
3 (b+c) + a (b+c) = 30
3 (b+c) + 2 (b+c) = 30
(b+c)(3+2) = 30
5 (b+c) = 30
b+c = 6
2a + ab + ac = 63
2a + a (b+c) = 63
2a + 7a = 63
9a = 63
a = 7
27. a = 2
3b + 3c + ab + ac = 30
3 (b+c) + a (b+c) = 30
3 (b+c) + 2 (b+c) = 30
(b+c)(3+2) = 30
5 (b+c) = 30
b+c = 6
2a + ab + ac = 63
b + c = 7
a ( 2 + b + c ) = 63
a ( 2 + 7 ) = 63
a x 9 = 63
a = 63 : 9
a = 7
3a + 3c + ab + ac = 30
a = 2
b + c = ?
3 ( a + c ) + a ( b + c ) = 30
3 ( 2 + c ) + 2 ( b + c ) = 30
( b + c ) x ( 3+ 2 ) = 30
( b + c ) x 5 = 30
b + c = 30 : 5
b + c = 6
b + c = 7
a ( 2 + b + c ) = 63
a ( 2 + 7 ) = 63
a x 9 = 63
a = 63 : 9
a = 7
3a + 3c + ab + ac = 30
a = 2
b + c = ?
3 ( a + c ) + a ( b + c ) = 30
3 ( 2 + c ) + 2 ( b + c ) = 30
( b + c ) x ( 3+ 2 ) = 30
( b + c ) x 5 = 30
b + c = 30 : 5
b + c = 6